Risk factors for age related maculopathy in a Japanese population: the Hisayama study. Issue 4 (1st April 2003) - Miyazaki, M; Nakamura, H; Kubo, M; Kiyohara, Y; Oshima, Y; Ishibashi, T; Nose, Y
Abstract : Aims: To examine the risk factors for age related maculopathy (ARM) in a sample Japanese population. Methods: In 1998, a cross sectional community survey was conducted among residents of Hisayama. A total of 596 men and 886 women living in Hisayama, Japan, aged 50 years or older consented to participate in the study. Each participant underwent a comprehensive examination that included an ophthalmic examination. The presence of ARM was determined by grading from fundus examination by indirect ophthalmoscopy, slit lamp examination, and colour fundus photographs. Using these cross sectional data, logistic regression analyses were performed to determine the risk factors for ARM. The following 10 possible risk factors were used: age, cataract, hypertension (history), hypertension (history or examination), diabetes, hyperlipidaemia, current smoker, alcohol intake, BMI, and WBC. Results: ARM was detected in 19.5% of men and 14.9% of women. Men were found to have a significantly higher prevalence of ARM than women. Multiple logistic regression analysis showed that age and hypertension (history or examination) were significantly associated with ARM in men, whereas only age was a significant risk factor for ARM in women. Conclusions: This study suggests that higher age and male sex are relevant risk factors for ARM in Japan. In addition, hypertension is a relevant risk factor in men.